PENGARUH INTENSITAS PENGGUNAAN SOSIAL MEDIA TIKTOK DAN INTENSITAS KOMUNIKASI DENGAN TEMAN SEBAYA TERHADAP TINGKAT SELF DISCLOSURE PEREMPUAN PADA KONTEN KECANTIKAN DI TIKTOK - Amelia Jasmine Rahayu; Nuriyatul Lailiyah (Interaksi Online, 2026)
Freedom of expression has made TikTok a space where users can share their feelings, opinions, and daily activities without hesitation. However, this creative freedom may also trigger excessive self-disclosure, which can potentially endanger users themselves. The purpose of this study is to determine the influence of TikTok social media usage intensity on women’s self-disclosure in beauty content and to identify the influence of peer communication intensity on women’s self-disclosure in beauty content. This study employs a quantitative method with an explanatory approach. The population consists of 2,799 students from the Faculty of Social and Political Sciences at Diponegoro University, Semarang, with a sample size of 100 students. Data analysis was conducted using multiple linear regression, coefficient of determination, F test, and t-test. The results indicate that TikTok social media usage intensity and peer communication intensity have a positive and significant influence on self-disclosure. The coefficient of determination (adjusted R square) is 0.793, meaning that both independent variables explain 79.3% of women’s self-disclosure in beauty content